2000
DOI: 10.1002/1096-9861(20000101)429:1<166::aid-cne13>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Subunit composition and novel localization of K+ channels in spinal cord

Abstract: Axonal K+ channels involved in normal spinal cord function are candidate targets for therapeutics, which improve sensorimotor function in spinal cord injury. To this end, we have investigated the expression, localization, and coassociation of Kv1 alpha and beta subunits in human, rat, and bovine spinal cord. We find that Kv1.1, Kv1.2, and Kvbeta2 form heteromultimeric complexes at juxtaparanodal zones in myelinated fibers. However, these same complexes are also present in paranodal regions of some spinal cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 45 publications
4
36
0
Order By: Relevance
“…Myelinating glial cells form septate like junctions with the paranodal axonal membrane; these appear to be the key to precise localization of ion channels on axons. 84 Our group and others have shown that the dysfunctional properties of the surviving demyelinated axons are associated with changes in the distribution and expression of Kv1.1 and Kv1.2 K + channels. 4,34,35,52,67,68,92,101 Indeed, axonal conduction deficits in various in vitro and in vivo models of traumatic demyelination or genetic dysmyelination are partially restored after application of 4-aminopyridine, a K + -channel antagonist.…”
Section: Posttraumatic Changes In Spinal Cord White Mattermentioning
confidence: 96%
“…Myelinating glial cells form septate like junctions with the paranodal axonal membrane; these appear to be the key to precise localization of ion channels on axons. 84 Our group and others have shown that the dysfunctional properties of the surviving demyelinated axons are associated with changes in the distribution and expression of Kv1.1 and Kv1.2 K + channels. 4,34,35,52,67,68,92,101 Indeed, axonal conduction deficits in various in vitro and in vivo models of traumatic demyelination or genetic dysmyelination are partially restored after application of 4-aminopyridine, a K + -channel antagonist.…”
Section: Posttraumatic Changes In Spinal Cord White Mattermentioning
confidence: 96%
“…Saltatory conduction at nodes is secured by the juxtaparanodal expression of Kv1.1 and Kv1.2 channels, and by the nodal expression of Kv3.1b and Kv7.2/Kv7.3, which all concur to reduce reexcitation of the axon (152,154,165,378,435,550,551,584,585). Other calcium-or sodium-activated potassium channels are encountered in the nodal region of myelinated axons (see Table 2).…”
Section: Channels In the Nodes Of Ranviermentioning
confidence: 99%
“…To verify the absence of Kv␤2 protein in the null animals, we evaluated central and peripheral nervous system tissues from Kv␤2-null mice using a monoclonal antibody directed against the N-terminal region of the protein. We focused on two regions of the nervous system where colocalization of Kv1.1/Kv1.2/Kv␤2 has been extensively studied: the terminals of cerebellar basket cells and the juxtaparanodes of myelinated nerves (29). As shown in Fig.…”
Section: Kv11/kv12 Trafficking and Biogenesis In Kv␤2-null Mutants-ifmentioning
confidence: 99%